Imperative Sentence in “The Guidance iPhone Support Website” - I Gusti Bagus Wahyu Nugraha Putra; IB Gede Nova Winarta; Puspita Dewi, Ni Made (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2021)
This study attempts to describe imperative sentence in “The Guidance iPhone Support Website”. The aim of this study to investigate the types of imperative sentences and to determine the constituent structure by using tree diagram. The data were collected through library research by reading the e-guidance, note taking and classifying the data based on imperative sentence. The analysis of the data was conducted qualitative method and presented descriptively based on the theory proposed by Quirk et al. (1985) in classifying the types of imperative sentence and the theory proposed by Brown and Miller (1991) is used in analysing the constituent structure by using tree diagram. The method that applied in presenting the result of the analysis was used formal and informal methods. There are two types of imperative sentences found In “The Guidance of iPhone Support Website”, as follows: imperative without subject with a total of 242 or 98,4% and negative imperative with a total of 4 or 1,6%. The constituent structure of imperative sentence is described by tree diagram. The constituent of imperative sentence found in data consists of an omitted subject and negative form.